Artistic Memorial Facilities as a Phenomenon of Impact on Emotional Psychological Perception of People - Karlygash, Kanybekova; Roslykova, Y.; Kulbayeva, M.; Koshkimbayev, K.; Elantsev, A.; Shaikynbekova, R.; Umbetyarova, L. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The interplay between architectural design and human psychology is significant, yet it remains largely unnoticed or even ignored both in and outside the design industry. Moreover, the relationship between design and psychology is not only consequential and is bidirectional. On the one hand, successful design has been shown to have clear psychological and physiological impacts; on the other, psychology, human experience, and the function of our neurological systems all play a significant role in what we perceive to be a successful design. This thesis endeavors to understand how that complex relationship evolved and how it works in today's world and shows how artistic memorial facilities can help emotionally to people. The architectural style has evolved over time as the general public's preferences have changed and as new materials and building processes have been discovered. Some styles have been fads that have quickly come and gone, while others have stood the test of time and been around for centuries, even influencing some modern architecture today. The socio-political, socio-cultural processes taking place in modern society require a serious rethinking of the spiritual, moral, cultural, and historical values underlying the artistic and aesthetic comprehension of the world by students. The problem of the aesthetic education of the younger generation, the gradual revival of traditions and culture of peoples is acquiring special relevance at present. At the same time, interest in studying the problems of introducing young people to culture, particularly works of art of architecture - architectural monuments, is of great importance. Of course, the issues of the beneficial influence of the architectural and spatial environment on the development of artistic creativity of children, instilling in schoolchildren a desire to join the national artistic culture with the help of the heritage of ancestors as a factor in the aesthetic education of schoolchildren, enrichment of their inner world are also relevant. The preceding determines the need for further research of art and pedagogical education and aesthetic education of schoolchildren based on a deep study of the heritage of their ancestors, and above all on the historical and architectural samples of cultural and art monuments. This paper aims to show the development of artistic forms of memorial facilities in Kazakhstan and describe how it will emotionally help people. As well as depict its historical development and significance to the people. This research starts its analysis from ancient times until now with memorable periods in history.